1993
DOI: 10.1007/bf00454896
|View full text |Cite
|
Sign up to set email alerts
|

The spatial patterns of ?/A4 deposit subtypes in Alzheimer's disease

Abstract: The spatial patterns of diffuse, primitive, classic (cored) and compact (burnt-out) subtypes of beta/A4 deposits were studied in coronal sections of the frontal lobe and hippocampus, including the adjacent gyri, in nine cases of Alzheimer's disease (AD). If the more mature deposits were derived from the diffuse deposits then there should be a close association between their spatial patterns in a brain region. In the majority of tissues examined, all deposit subtypes occurred in clusters which varied in dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…Studies also suggest that SP and NFT exhibit distinct but independently distributed topographic patterns in the cerebral cortex in AD [12,64]. Braak and Braak [22] showed that tau pathology occurred first in entorhinal cortex, often in the absence of SP, whereas the subsequent spread and distribution of Aβ was more variable.…”
Section: Is the Formation Of Neurofibrillary Tangles Related To Aβ?mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also suggest that SP and NFT exhibit distinct but independently distributed topographic patterns in the cerebral cortex in AD [12,64]. Braak and Braak [22] showed that tau pathology occurred first in entorhinal cortex, often in the absence of SP, whereas the subsequent spread and distribution of Aβ was more variable.…”
Section: Is the Formation Of Neurofibrillary Tangles Related To Aβ?mentioning
confidence: 99%
“…Perez et al [103], however, showed that Aβ [25][26][27][28][29][30][31][32][33][34][35] could result in tau aggregation and that a decrease in Aβ aggregation was induced by tau peptides. Hence, aggregation of tau may be correlated with disassembly of Aβ which could explain the lack of spatial correlation [12]. In addition, SP and NFT may be temporally separated in the brain [82].…”
Section: Is the Formation Of Neurofibrillary Tangles Related To Aβ?mentioning
confidence: 99%
“…Many studies fail to support the hypothesis that diffuse plaques evolve into dense-core plaques over time [2,38,60,65,72] suggesting that all plaques are not created equally, and that distinctive plaque types do not exchange in the brain [11,12,14,46,72]. For example, the majority of the A␤ deposits in the APP22 mice are the diffuse type, while those detected in the APP23 mice develop almost exclusively the dense-core, congophilic at their first appearance making it very difficult to reconcile the diffuse plaque types form a precursor for the dense-core congophilic plaques [60].…”
Section: Unique Mechanisms Of Plaque Formationmentioning
confidence: 99%
“…The pathology may then spread among cortical gyri and to subcortical regions via cortico-cortical and cortical-subcortical pathways respectively [5,45,136]. This hypothesis is supported by studies of the spatial patterns of SP and NFT [6,13] and of transgenic mice, in which there is selective disruption of cortico-cortical pathways [47]. Furthermore, this pattern of neurodegeneration correlates with specific neurotransmitter deficits, e.g., acetylcholinesterase-immunoreactive neurites are present at the periphery of SP, which could represent the degeneration of ascending and cortical cholinergic pathways [157].…”
Section: Anatomymentioning
confidence: 94%